Design of Compact Dual-Polarized Antennas for MIMO Handsets - Wenhua Chen; Xin Wang; Zhenghe Feng (International Journal of Antennas and Propagation)
A design method of compact dual-polarized antennas has been proposed for multiple input and multiple output (MIMO) handset application. For the sake of high isolation in dual polarizations, a printed monopole and a hybrid slot antenna are combined using a coplanar waveguide (CPW) and microstrip hybrid feeding structure. The proposed topology will result in orthogonal current distribution modes for the different polarizations, which effectively reduces the mutual coupling of the two modes. The operation mechanism of the feeding structure is analyzed in principle and verified by simulation. Simulated and measured results show this compact dual-polarized antenna achieves isolation between the two ports of better than 25 dB, and the relative bandwidth is wider than 23.5%.